Effect of Resin Cement Type on the Microtensile Bond Strength to Lithium Disilicate Ceramic and Dentin Using Different Test Assemblies - Salazar Marocho, Susana Maria [UNESP]; Oezcan, Mutlu; Amaral, Regina [UNESP]; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (Quintessence Publishing Co Inc, 2013)
Purpose: This study evaluated the microtensile bond strength (mu TBS) of 3 different resin cements to lithium-disilicate ceramic using two assemblies: ceramic-cement-ceramic (CCC) and ceramic-cement-dentin (CCD).Materials and Methods: The bonding surfaces of lithium disilicate ceramic blocks (5 x 5 x 4 mm) (N-block = 90) were etched with 4% hydrofluoric acid for 20 s and silanized. Flat dentin surfaces of human third molars were conditioned according to the respective manufacturer's specifications for three types of resin cements (ML: Multilink, Ivoclar-Vivadent; PF: Panavia F, Kuraray; SB: Super Bond C&B, Sun Medical). While one set of ceramic blocks (n = 30) was cemented to another equal set (CCC assembly), another set of ceramic blocks (n = 30) was cemented on flat dentin (CCD assembly). The bonded specimens were stored in distilled water at 37 degrees C for 24 h, and then sectioned along the x- and y-axes to obtain nontrimmed beam specimens. The beam specimens were randomly divided into two conditions: dry condition (DC - immediate testing); and aging condition (AC - thermocycling 12,000 times + water storage for 150 days). The mu TBS bond strength test was performed using a universal testing machine (1 mm/min). After debonding, the substrate and adherent surfaces were analyzed using a scanning electron microscope to categorize the failure types. The data were statistically evaluated using 2-way ANOVA and Tukey's test (5%).Results: While the mean mu TBS of CCC assemblies were significantly influenced by the cement type (p < 0.05) and aging (p < 0.05), CCD assemblies showed a significant effect of the cement (p < 0.05) but not the aging (p > 0.05). Without aging (DC), the mean mu TBS (MPa) of SB (26.9) and PF (26.9) were significantly higher than ML (18.5) (p < 0.05). For CCC after aging (AC), SB (26.6) showed higher mean mu TBS than those of PF (16.4) and ML (18.5) (p < 0.05). However, in CCD after AC, no significant difference was found between the groups (p > 0.05). In both CCC and CCD assemblies, pre-test failures were the least with SB cement. Regardless of the resin cement type employed and storage conditions, adhesive failures ranged between 35.3% and 88.9%, cohesive failures in cement between 2.3% and 35.3%, and cohesive failures in ceramic between 3.3% and 6.8%.Conclusion: SB resin cement demonstrated the highest bond strength to a lithium disilicate ceramic in both tests assemblies with and without aging conditions.
Keywords: adhesion; aging; bond strength; ceramic; dentin; lithium disilicate; microtensile bond strength